Habitual natto intake elevates serum MK-7 levels, enhances osteocalcin carboxylation, and supports bone density: a meta-analysis of Japanese evidence - Wen, Zhixiang; Zhen, Mengqi; Wang, Jing; Agudamu, Agudamu; Zhang, Yang (Frontiers in Nutrition, 2025)
ObjectiveNatto, a traditional Japanese fermented soybean food, is the richest natural source of menaquinone-7 (MK-7), a form of vitamin K2 involved in osteocalcin activation and bone mineralization. This study aimed to systematically evaluate the effects of habitual natto consumption on serum MK-7 concentrations, osteocalcin carboxylation status, and bone mineral density (BMD) in Japanese populations.MethodsWe searched PubMed, Web of Science, and Scopus through January 2025. Eligible studies compared habitual natto consumers with low- or non-consumers and reported outcomes for serum MK-7, carboxylated or undercarboxylated osteocalcin (OC/ucOC), or BMD. Certainty of evidence was assessed using the GRADE framework. Random-effects meta-analyses were performed using Cohen's d and 95% confidence interval (CI).ResultsSix observational and quasi-experimental studies (N = 2,327) met inclusion criteria. Natto intake is associated with significantly elevated serum MK-7 [d = 2.10, 95% CI (1.55, 2.66) after sensitivity analysis removing an outlier], increased OC [d = 0.26, 95% CI (0.08, 0.43)], decreased ucOC [d = −0.50, 95% CI (−0.74, −0.26)], and modestly greater BMD across sites [d = 0.65, 95% CI (0.09, 1.21); sensitivity analysis: d = 0.35, 95% CI (0.21, 0.48)]. The certainty of evidence ranges from moderate for serum MK-7 to low or very low for osteocalcin and BMD outcomes, reflecting the predominance of observational designs and remaining imprecision. Publication bias appears minimal.ConclusionsHabitual natto consumption is associated with improved vitamin K status and bone metabolism markers. However, given the observational nature of the available evidence and its moderate-to-low certainty, these findings should be interpreted with caution. Natto may represent a culturally grounded dietary approach for supporting bone health and osteoporosis prevention, but its generalizability beyond Japanese populations warrants further investigation.